2017
DOI: 10.21474/ijar01/3873
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Back the Lost Value of Philippine Edible Ferns: Their Antioxidant, Proteins and Utilization.

Abstract: Ferns have myriad compounds and are used by native people as food for a long time but this use seems to diminish over time. Knowing their use as food, bioactives and proteins were determined to demonstrate their health and wellness benefits. Ten species of edible ferns were collected and propagated in the Pteridogarden. The young sterile fronds were used to determine bioactives and proteins. The bioactives were determined by thin layer chromatography, DPPH assay, Bradford assay and SDS-PAGE. A seminar-field vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The antioxidant properties of ferns are not new; in fact, extracts of some ferns, such as Pityrogramma calomelanos and Polypodium leucotomos, were recently reported as antioxidants due to the presence of polyphenols and flavonoids [21,41]. Different types of flavonoids have been described on selected Aspleniaceae ferns [42] and in ferns of the Dryopteris genus [43].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant properties of ferns are not new; in fact, extracts of some ferns, such as Pityrogramma calomelanos and Polypodium leucotomos, were recently reported as antioxidants due to the presence of polyphenols and flavonoids [21,41]. Different types of flavonoids have been described on selected Aspleniaceae ferns [42] and in ferns of the Dryopteris genus [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, flavonoids (Malterud and Rydland, 2000), terpenoids (Amagata et al, 2003), allyl benzenes, allyloxy benzenes, heterocylic, and phenolic compounds (Sadeghian et al, 2015) are reported as 15-LOX inhibitors. Nevertheless, phytochemical screening of A. nidus also revealed the presence of compounds claimed to inhibit 15-LOX such as phenolic, terpene, and flavonoids (Amoroso et al, 2017). The presence of phytochemicals with known anti-inflammatory properties in the D. esculentum, D. quercifolia, and A. nidus extracts is further supported by their HPTLC profile.…”
Section: -Lipoxygenase Inhibition Activitymentioning
confidence: 85%
“…In addition, Chai et al (2015) have also reported a significant amount of phenolic and flavonoids in the aqueous extract of D. esculentum. The phytochemical screening via the TLC method by Amoroso et al (2017) also reported the detection of phenolics and flavonoids using potassium ferric cyanide-ferric chloride and vanillin/sulfuric acid as a confirmatory test.…”
Section: Range Of Rf Valuesmentioning
confidence: 99%
“…The plant extracts possess antibacterial [ 273 ], anti-inflammatory [ 274 ], antioxidative [ 275 ] and antidiabetic activities [ 276 ].…”
Section: Distribution Ethnomedicine Pharmacognosy and Phytochemistry ...mentioning
confidence: 99%